Arranjo espacial, densidade e época de semeadura no acúmulo de matéria seca e nutrientes de três adubos verdes - Lima, Juliana Domingues [UNESP] (2010)
The main objective of the study was to evaluate the effect of sowing densities, spatial arrangements and sowing dates in the accumulation of dry matter and nutrients in Crotalaria juncea, Mucuna deeringiana, and Cajanus cajan, in Pariquera-Açu, Vale do Ribeira, São Paulo State, Brazil. Three experiments were carried out: 1) sowing density x green manures, 2) spatial arrangement x green manures, and 3) sowing date x green manures. The experimental design was randomized complete blocks, with four replications, with the first experiments in a factorial scheme and the third in a split-plot arrangement. When plants reached 50% of flowering, the accumulation of dry matter, macronutrients, micronutrients, and organic carbon in the shoot were determined. Higher sowing densities reduce the accumulation of dry matter, B, and Zn, in Crotalaria juncea and Mucuna deeringiana; the accumulation of P in Mucuna deeringiana and Cajanus cajan; and the accumulation of N, S, and Cu in all green manures. The spatial arrangement does not affect the accumulation of dry matter and nutrients. Based on the accumulation of dry matter and nutrients, Crotalaria juncea is the most efficient species for use as green manure, when sown in November. Crotalaria juncea, Mucuna deeringiana, and Cajanus cajan show low performance in the accumulation of dry matter and nutrients, when sown at later dates.